2008
DOI: 10.1007/s12072-008-9064-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiles in patients with chronic hepatitis C: a case–control study

Abstract: BackgroundThe clinical implications of metabolic profiles in patients with chronic hepatitis C remain controversial. To study the association of metabolic abnormalities with chronic hepatitis C, we conducted a case-control study with special emphasis on serum lipid pattern, fasting blood glucose, and adiponectin. Methods We enrolled 500 patients with chronic hepatitis C and 536 sex and age-matched controls. Unadjusted and adjusted associations of demographic and metabolic variables were estimated. Results Chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 46 publications
2
34
1
2
Order By: Relevance
“…(23). Çalışmamızda, HCV pozitif HD hastalarında HCV negatif hastalara göre serum TG düzeyleri daha düşük bulundu.…”
Section: Keyunclassified
See 1 more Smart Citation
“…(23). Çalışmamızda, HCV pozitif HD hastalarında HCV negatif hastalara göre serum TG düzeyleri daha düşük bulundu.…”
Section: Keyunclassified
“…HCV'li hastalarda HDL düzeylerindeki düşüklüğün nedeni kesin olarak bilinmemekle birlikte, kronik inflamasyon sonucu karaciğerde oluşan hasarın lipoprotein sentezini bozmasına bağlı olabileceği düşünülmüştür (18,26). Karaciğerdeki kronik inflamasyonun LDL ve HDL düzeylerini azaltarak hipokolesterolemiye neden olduğu bilinmektedir (7,23). Çalışmamızda, hemodiyalize giren HCV pozitif hastalarda HCV negatif hastalara göre serum HDL düzeyleri daha düşük idi.…”
Section: şAhin İ Ve Arkunclassified
“…For instance, several studies found patients with chronic hepatitis C to have significantly lower cholesterol levels than those with chronic hepatitis B infection, suggesting that the alteration in lipids observed in hepatitis C infection is virus-specific. [2][3][4] Further, when stratifying by pretreatment levels of alanine aminotransferase or hepatitis C RNA, we found no difference in rebound levels of cholesterol or LDL, suggesting that the degree of hepatic inflammation or level of viremia does not influence cholesterol or LDL levels. We are not aware of any studies evaluating the change in serum LDL and cholesterol levels following viral suppression during hepatitis B therapy, but agree that such evaluation would allow this question to be definitely answered.…”
mentioning
confidence: 60%
“…Our previous case-control study consistently showed lower cholesterol and LDL levels in patients with chronic hepatitis C than in uninfected controls. 2 However, HCV infection was associated with a higher cholesterol level in patients with normal alanine aminotransferase (ALT) levels, 2 suggesting ALT level, a biomarker of hepatic inflammation, may play a role in modulating the relationship between HCV infection and lipid metabolism. Another study also reported a significant decrease of cholesterol level in patients with chronic active hepatitis compared to healthy controls.…”
mentioning
confidence: 99%
“…In addition, serum lipid profiles of CHC patients are different from healthy or other disease control subjects. For example, CHC patients usually have lower serum triglyceride, total cholesterol, but higher serum adiponectin, homeostasis model assessment (HOMA)-insulin resistance index, and serum high-density lipoprotein (HDL) levels than matched healthy adults [9]. Moreover, serum HCV RNA levels were positively proportional to HOMA-insulin resistance index, serum triglyceride, and total cholesterol levels in CHC patients [10,11].…”
mentioning
confidence: 99%